Integration of disability sport in the Norwegian sport organizations: Lessons learned - Soerensen, M.; Kahrs, N. (Adapted Physical Activity Quarterly, 2006)
The Norwegian Olympic Committee and Confederation of Sports` commitment to integrate disability sport in the sport organizations for the able-bodied was evaluated based upon a description of an ideal, inclusive sports organization. Data were collected primarily through interviews and questionnaires. The results indicate that the integration process proceeded more slowly than originally intended. There were still unresolved matters on the structural/organizational level, and the sports federations` officials were uncertain about the extent of their responsibility and the role of the new sports organization for persons with a disability. More relevant competence was needed in the organization. All organizations reported improved attitudes toward individuals with a disability and indicated that integration was a demanding enterprise.